(untitled) (Proceeding of the International Conference on Arts and Humanities, 2024)
In today’s era, science and technology are crucial keys to innovation and creativity, connecting all fields such as technology, engineering, commerce, and art, as well as connecting artists, researchers, educators, and technologists to create a development era with many changes, new forms, and more choices. In Vietnam in general and Ho Chi Minh City in particular, innovation and technological development have drastically changed almost every aspect, especially the fashion industry, in which the most prominent influences and changes have been in traditional wedding attire. Science and technology have brought many conveniences and innovations to traditional wedding attire, such as accelerating the production process, mass production, and precision cutting and sewing equipment; Vietnamese wedding attire undergoes changes in diverse styles, colors, and artistic decorations in line with global fashion trends or changes in accompanying accessories, meeting all consumer needs. However, alongside these advantages, many elements could affect artistic and humanitarian values, ethics towards society and individuals, and even cultural identity in traditional wedding attire. This trend is particularly evident in the current aesthetic preferences for wedding attire, such as scanty, overly thin, or see-through styles. Traditional attire is an invaluable asset, the core of national identity, and the foundation for creating new values and cultural exchanges. Therefore, research through data collection, information synthesis, and analysis is necessary to highlight the key issues that have shaped the mainstream of traditional wedding fashion in Vietnam, specifically in Ho Chi Minh City, under the influence of science and technology. This research gives comments and determines aesthetic directions to build, develop, and still preserve the cultural identities of traditional wedding attire in Ho Chi Minh City and the country as a whole.